3D models of chondrocytes within biomimetic scaffolds: Effects of cell deformation from loading regimens. (October 2020) - Di Federico, Erica; Bader, Dan L.; Shelton, Julia C.
Abstract: Background: Mechanical conditioning has been widely used to attempt to enhance chondrocyte metabolism for the evolution of functionally competent cartilage. However, although upregulation of proteoglycans have been reported through the application of uniaxial compression, minimal collagen has been produced. The study is designed to examine whether alternative loading regimens, equivalent to physiological conditions, involving shear in addition to compression can enhance collagen production. Methods: Finite element models were developed to determine how the local chondrocyte environments within agarose constructs were influenced by a range of static and dynamic loading regimens. 3-D poro-viscoelastic models were validated against experimental data. In particular, these models were used to characterise chondrocyte deformation in compression with and without shear superimposed, with special reference to the formation of pericellular matrix around the cells. Findings: The models of the hydrogel constructs under stress relaxation and dynamic cyclic compression conditions were highly correlated with the experimental data. The cell deformation ( y / z ) in the constructs was greatest in the centre of the constructs, increasing with magnitude of compression up to 25%. The superposition of shear however did not produce significant additional changes in deformation, with the presence of PCM reducing the chondrocyte deformation. Interpretation: The use of FE models can prove important in the definition of appropriate, optimised mechanical conditioning regimens for the synthesis and organisation of mature extra cellular matrix by chondrocyte-seeded constructs. They will also provide insight into the mechanisms relating cell deformation to mechanotransduction pathways, thereby progressing the development of functionally competent tissue engineered cartilage. Highlights: FE models can predict chondrocyte deformation in constructs under static and dynamic loading. Superposition of shear on compression does not produce significant changes in cell deformation. Pericellular matrix resulting from cell activity reduces chondrocyte deformation. Modelling highlights the importance of cell deformation in mechanotransduction pathways. Modelling offers the potential of optimising the development of functional cartilage.